Kesalahan siswa dalam menyelesaikan soal tipe HOTS (meta analisis) - Elfi Rahmadhani; Hilliyani Hilliyani (IKIP Siliwangi, 2023)
This study aims to see the types of mistakes students make in solving HOTS type math problems as well as what mistakes they make. This type of research is a meta-analysis research. Sources of data are obtained by tracing research results in the form of national journals through Google Scholar, and references contained in journals. The analysis was carried out using content analysis techniques. Based on the search results obtained 14 articles relevant to the research title, and analyzed using descriptive qualitative analysis. Based on the results of the analysis, it is known that, there are 3 types of error analysis, namely 1) Newman error analysis (NEA). 2) Hadar error analysis. 3) Analysis of the errors found by the researcher. The mistakes made by students were misconceptions, calculations, techniques, understanding, not solving questions, and students being less careful.